2021
DOI: 10.3390/oceans2040045
|View full text |Cite
|
Sign up to set email alerts
|

Response of Tropical Cyclone Frequency to Sea Surface Temperatures Using Aqua-Planet Simulations

Abstract: The present study investigates the effect of increasing sea surface temperatures (SSTs) on tropical cyclone (TC) frequency using the high-resolution Australian Community Climate and Earth-System Simulator (ACCESS) model. We examine environmental conditions leading to changes in TC frequency in aqua-planet global climate model simulations with globally uniform sea surface temperatures (SSTs). Two different TC tracking schemes are used. The Commonwealth Scientific and Industrial Research Organization (CSIRO) sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
(120 reference statements)
1
1
0
Order By: Relevance
“…The earlier studies note that either increased saturation deficit/entropy deficit of the atmosphere 30 , 31 , 41 or reduced upward mass flux 27 influence the TC frequency statistics for future warmer climates. Our study agrees with earlier studies 29 , 42 , which note that both the mechanisms act simultaneously (i.e., increased moisture entropy deficit/reduced mid-level moisture reduces the upward mass flux) in explaining the response of TC frequency to climate change. In further examining the NH summer of the MIS5e and 2×CO 2 simulations, we observe a striking difference between the two simulations in terms of the movement of the ITCZ.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The earlier studies note that either increased saturation deficit/entropy deficit of the atmosphere 30 , 31 , 41 or reduced upward mass flux 27 influence the TC frequency statistics for future warmer climates. Our study agrees with earlier studies 29 , 42 , which note that both the mechanisms act simultaneously (i.e., increased moisture entropy deficit/reduced mid-level moisture reduces the upward mass flux) in explaining the response of TC frequency to climate change. In further examining the NH summer of the MIS5e and 2×CO 2 simulations, we observe a striking difference between the two simulations in terms of the movement of the ITCZ.…”
Section: Discussionsupporting
confidence: 93%
“…S2). It has previously been demonstrated that large-scale increases in atmospheric stability led to a reduction in TC frequency 27 29 . In addition, increased values of the moist-entropy deficit provide unfavorable conditions for TC formation, which reduces the extent of the sustained atmospheric convection during the genesis stage of a storm 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%